Method sections of management research articles: a pedagogically motivated qualitative study. - Lim, Jason Miin Hwa (Elsevier, 2006)
Notwithstanding the voluminous literature devoted to research genres, more investigation needs to be conducted to demonstrate the pedagogical significance of studying linguistic features in relation to communicative functions. Motivated by a concern for the pedagogical applicability of genre analysis, this paper investigates the extent to which results of an analysis may be effectively employed for the second language acquisition of syntactic structures and lexical items commonly found in the Method sections of management research articles. On the basis of the data analyzed, I suggest that writing courses in tertiary institutions should be tailored to meet the needs of students encountering di?culties in associating linguistic features with communicative functions of academic texts. Using an innovative and comprehensible approach to describing the steps under each rhetorical move, I have provided relevant materials that may be usefully exploited in the teaching of the genre specifications of the Method sections of management research articles. Despite the acknowledgment that no single model can be considered entirely appropriate for learners in different academic disciplines, reasons are given to explain why constituent steps should be investigated in sufficient detail if ESP teachers are to provide a pedagogically meaningful model for second language learners in a particular discipline.